2014
DOI: 10.1371/journal.pone.0090350
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations, Efficacy and Safety of Efavirenz in HIV-Infected Adults Treated for Tuberculosis in Cambodia (ANRS 1295-CIPRA KH001 CAMELIA Trial)

Abstract: ObjectiveTo assess efavirenz plasma concentrations and their association with treatment efficacy and tolerance of efavirenz 600 mg daily in HIV-tuberculosis co-infected patients.MethodsHIV-infected adults with CD4+ T cell count ≤200/mm3 received standard 6-month tuberculosis treatment and antiretroviral therapy including a daily-dose of 600 mg of efavirenz, irrespective of their body weight. Mid-dose blood samples were drawn both on tuberculosis treatment (week +2 and week +6 after antiretroviral therapy initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…However, plasma concentration median in our study population was higher than all others studies conducted in Africa, which is very close to that found by Gounden et al (3,980 µg/L) in South Africa [12]. But the median observed in our study was strangely higher than those found by Sarfo et al (1,087 µg/L) or Gunda et al (2,112 µg/L) respectively in Ghana and Tanzania [13][14]. Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L.…”
Section: Efavirenz Plasma Concentrationssupporting
confidence: 81%
“…However, plasma concentration median in our study population was higher than all others studies conducted in Africa, which is very close to that found by Gounden et al (3,980 µg/L) in South Africa [12]. But the median observed in our study was strangely higher than those found by Sarfo et al (1,087 µg/L) or Gunda et al (2,112 µg/L) respectively in Ghana and Tanzania [13][14]. Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L.…”
Section: Efavirenz Plasma Concentrationssupporting
confidence: 81%
“…By contrast, a study of 80 South African patients, with a median efavirenz concentration of 3.98 mg/L, found that the proportion of patients with high efavirenz concentrations was 40% . Another study with 540 Cambodian patients, with a median (IQR) efavirenz concentration at week 50 of 2.77 (1.94, 3.98) mg/L, found that proportion to be 20–30% . A recent study from Taiwan reported a median efavirenz concentration (IQR) of 2.82 (0.98–10.00) mg/L, and 22.2% of subjects had high efavirenz concentrations after at least 2 weeks of efavirenz treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the median plasma efavirenz concentration increased from 3.02 to 3.71 mg/L from week 4 to week 48; such findings were not reported in previous studies , and the mechanism of such an increase over time remains unclear. We speculate that one possibility is improved adherence over time.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to predict safety and efficacy of EFV have focused on characterizing the systemic pharmacokinetics (12,22,23). Borand et al (24) found no association between treatment failure and the recommended efavirenz concentrations in plasma below 1 mg/liter (6). This may suggest that a lack of knowledge of the relationship between plasma and intracellular concentrations of EFV limits the ability to fully understand the pharmacokinetic-pharmacodynamic relationships of EFV and to predict treatment and toxicity outcomes.…”
Section: Discussionmentioning
confidence: 99%